Richer, greener, and more thermophilous? – a first overview of global warming induced changes in the Italian alpine plant communities within the new GLORIA ITALIA NETWORK. (2nd January 2022) - Porro, Francesco; Orsenigo, Simone; Abeli, Thomas; Mondoni, Andrea; Corli, Anna; White, Fiona J.; Lodetti, Silvano; Tomaselli, Marcello; Petraglia, Alessandro; Carbognani, Michele; Gualmini, Matteo; Forte, T'ai G. W.; et al.
Abstract: We announce the formation of the "GLORIA ITALIA NETWORK" and present an overview of the Italian alpine plant communities changes that have occurred in the last 20 years. This network will provide coordination between Italian GLORIA sites and enhance public awareness of changes in alpine plant diversity under climate change.